Pengaruh Penyuluhan Gizi Tentang Obesitas Menggunakan Media Animasi terhadap Pengetahuan dan Sikap Pada Remaja di SMP Negeri 1 Lubuk Pakam - Inggita Senosa Ginting; Abdul Hairuddin Angkat; Sudana Fatahillah Pasaribu; Wanda Lestari (Lembaga Pengembangan Kinerja Dosen, 2024)
Obesity is a result of excessive energy consumption, this excess energy is stored in the body as fat, so that over time the body becomes heavier. This condition can be experienced by everyone, regardless of gender group or group of teenagers to adults. The aim of the research is to determine the effect of nutritional education about obesity using animation media on knowledge and attitudes in obese adolescents. This research was conducted at SMP Negeri 1 Lubuk Pakam. The research was conducted in May 2023 with quantitative methods using a Group Pre and Post Test design. Intervention in the form of counseling using animation media was given 3 times. The population in this study was class VIII, 319 students. The sample in this study was 32 obese students who met the criteria for being a sample. Data were collected using a knowledge and attitude questionnaire using a statistical test, namely the T-dependent test. The research results showed that the average knowledge of teenagers about obesity before counseling was 10.09, after being given counseling was 13.25 with a significant value of p=0.000. The average attitude score before being given counseling was 39.53, after being given counseling was 51.19 with a significant value of p=0.000. The conclusion of this research is that there is an influence of nutrition education about obesity using animation media on the knowledge and attitudes of teenagers at SMP Negeri 1 Lubuk Pakam. It is hoped that the school can play an active and creative role in providing health education about nutrition, especially about obesity in teenagers.